2022
DOI: 10.3389/fpubh.2022.954897
|View full text |Cite
|
Sign up to set email alerts
|

Congruence and discrepancy in Asian American women's perception and stress appraisal of gendered racial microaggressions: Relationships with depressive symptoms and internalized racism

Abstract: Prior research demonstrates significant links between discrimination and mental health by assessing either encounters with or stress appraisal of discrimination. However, research has yet to examine the dynamic interplay between frequency and stress appraisal (e.g., high frequency-low stress appraisal) and their linkage to depressive symptoms. Using a sample of 309 Asian American women (Mage = 22.81, SD = 0.26), we used a polynomial regression and response surface analysis to model the congruence and discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Despite the limited research on its psychological cost, internalized racism has been linked to detrimental mental health outcomes for Asian Americans. For instance, different dimensions of internalized racism have been directly associated with depression and eroding self-concept and -esteem (Choi et al, 2017; David, 2010; Keum & Wong, 2022) or have been found to exacerbate the link between racism and mental distress (Garcia et al, 2019) and suicidal ideation (Keum, Wong, et al, 2023).…”
Section: Covid-19-related Anti-asian Racismmentioning
confidence: 99%
“…Despite the limited research on its psychological cost, internalized racism has been linked to detrimental mental health outcomes for Asian Americans. For instance, different dimensions of internalized racism have been directly associated with depression and eroding self-concept and -esteem (Choi et al, 2017; David, 2010; Keum & Wong, 2022) or have been found to exacerbate the link between racism and mental distress (Garcia et al, 2019) and suicidal ideation (Keum, Wong, et al, 2023).…”
Section: Covid-19-related Anti-asian Racismmentioning
confidence: 99%
“…Internalized racism (i.e., self‐negativity) also interacted with gendered racial microaggressions in predicting suicidal ideation. Keum and Wong (2022) using polynomial regression examined the congruence and discrepancy between frequency and stress appraisal of gendered racial microaggressions among a sample of Asian American women and examined how these attitudes were related to depression and internalized racism. Their results suggested that greater congruence between frequency and stress was positively associated with depressive symptoms and internalized racism.…”
Section: Racial Microaggressions and Racismmentioning
confidence: 99%